2011
DOI: 10.1002/tcr.201100039
|View full text |Cite
|
Sign up to set email alerts
|

Contactless conductivity detection for electrophoretic microseparation techniques

Abstract: The technique of capacitively coupled contactless conductivity detection for electrophoretic separations is discussed. The position of the combination of the two techniques, which both rely on the control of the movement of ions in the electric field, is highlighted. A brief historical overview and an introduction into the fundamental mechanisms is also given, but this exploration focuses mainly on the unique aspects of the intimate interfacing between ionic conduction in the measuring cell and the electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…. Complementary data have also been published by Mai and Hauser , who reported that for C 4 D the LODs in CE are not significantly degraded when going to 10 μm capillaries and showed experimental data that also highlighted the improved resolution when going to narrower capillaries. Mai et al also showed that with capillaries of 10 μm, it is possible to employ a hydrodynamic flow concurrent with the electrophoretic separation.…”
Section: Fundamental Aspectssupporting
confidence: 78%
See 1 more Smart Citation
“…. Complementary data have also been published by Mai and Hauser , who reported that for C 4 D the LODs in CE are not significantly degraded when going to 10 μm capillaries and showed experimental data that also highlighted the improved resolution when going to narrower capillaries. Mai et al also showed that with capillaries of 10 μm, it is possible to employ a hydrodynamic flow concurrent with the electrophoretic separation.…”
Section: Fundamental Aspectssupporting
confidence: 78%
“…And in a recent publication Coltro et al reviewed the use of C 4 D in the microchip approach . A general overview of the main features of CE‐C 4 D has been given by Mai and Hauser . Please note that in the following discussions, the same reports may be referred to repeatedly in separate places when distinct aspects are touched on.…”
Section: Introductionmentioning
confidence: 99%
“…Prominent is the detection of species which do not absorb UV‐light and are thus not directly accessible on standard instruments fitted with a UV‐detector. Recent reviews discussing applications of C 4 D are available 39.…”
Section: Introductionmentioning
confidence: 99%
“…C 4 D has gained overwhelming popularity in recent years, being increasingly implemented both in capillary and microchip separation formats. As follows from a substantial fraction of available general literature , C 4 D drove out of common use other electrochemical detection techniques and significantly replaced conventional UV detection. A further iconic review on the developments and applications of CE with C 4 D, coauthored by Pavel Kubáň and Hauser , reveals that the method has been seeing a healthy growth, with an increasing number of reports based on using commercial detectors.…”
Section: Reviewsmentioning
confidence: 99%
“…A further iconic review on the developments and applications of CE with C 4 D, coauthored by Pavel Kubáň and Hauser , reveals that the method has been seeing a healthy growth, with an increasing number of reports based on using commercial detectors. Perhaps it is this tendency that allowed Mai and Hauser to conclude that the C 4 D has reached a degree of maturity so that new fundamental understandings or radical instrumental improvements are not very likely to occur. According to Matysik and coworkers , progress in C 4 D electronics and technology of detection cells is still perceptible.…”
Section: Reviewsmentioning
confidence: 99%